Preventif Care Melalui Media E-Booklet “Cerdi” dan Video Dapat Meningkatkan Pengetahuan dan Sikap Orang Tua dalam Pencegahan Diabetes Melitus pada Anak (Journal of Telenursing (JOTING), 2024)
This study aims to determine the effect of preventive care through “cerdi” e-booklet media and videos on parents' knowledge and attitudes in preventing diabetes mellitus in children. The research method used was a pre experimental One Group pretest posttest design. The results showed that preventive care through the media e-booklet “cerdi” and video obtained a p-value of 0.000. In conclusion, preventive care through “cerdi” e-booklet media and videos can improve parents' knowledge and attitudes in preventing diabetes mellitus in children. Keywords: E-Booklet, Parents, Prevention of Diabetes Mellitus in Children, Knowledge, Attitude, Video